Respuesta :

tqiu

Answer:

a=4, b=-3

Step-by-step explanation:

If it is vertical, then the y coefficient must be equal to zero, which means b = -3. When y is 0, a*3=2*3+6, which means a=4.

Answer:

a=4

b=-3

Step-by-step explanation:

ax+by=2x-3y+6 is vertical and passes through (3,0) which means the equation should be equivalent to x=3.

If we want the y's to cancel we need -3y on lefy since we have it on right so b=-3.

So now the equation is ax=2x+6

If ax=2x+6 and x=3, by substitution property we have a(3)=2(3)+6.

Let's solve for a.

3a=6+6.

3a=12

a=12/3

a=4.

a=4

b=-3

ACCESS MORE